2021
DOI: 10.3390/en14144096
|View full text |Cite
|
Sign up to set email alerts
|

How Policies Guide and Promoted Wind Power to Market Transactions in China during the 2010s

Abstract: Chinese wind power policies have productively promoted the development of wind power and also promoted the process of wind power participation in electricity market transactions. However, with policy emphasis on investment and neglect of utilization, there have been some difficulties in the development of Chinese wind power. To highlight the guiding role of policy and improve the wind power policy system, an analysis of Chinese wind power policies is conducted in this paper. First, aiming at the main component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Among the technologies used, wind energy is a promising option for mitigating these changes [89]. Due to the development and advancement of technology, the operating costs of installation and maintenance have been reduced in recent decades [90]. In addition, new devices and algorithms are constantly being developed to better identify and resolve faults in transmission systems.…”
Section: Us8180622b2mentioning
confidence: 99%
“…Among the technologies used, wind energy is a promising option for mitigating these changes [89]. Due to the development and advancement of technology, the operating costs of installation and maintenance have been reduced in recent decades [90]. In addition, new devices and algorithms are constantly being developed to better identify and resolve faults in transmission systems.…”
Section: Us8180622b2mentioning
confidence: 99%
“…It can be seen that the overhead line is mainly realized by placing several wires directly on the pole, and the general form of power supply is radial power supply. In the form of overhead line power supply, there are three main ways of supplying overhead lines, namely, radial, ring, and segmental contact [11]. In the form of radial power supply, it can be divided into dual power supply and single-side power supply with multiple segments and…”
Section: Figure2 the Basic Structure Of Overhead Linesmentioning
confidence: 99%
“…China is actively leading global climate governances to achieve reductions in carbon emissions [2][3][4]. In the 75th United Nations General Assembly, China made a commitment to reach carbon peak by 2030 and achieve carbon neutrality by 2060 [5]. At the Climate Ambition Summit 2020, UN Secretary General Guterres warned that the current commitments of all countries are far from enough to curtail the end-of-the-century global temperature rise to within 1.5 • C and further suggested that it may even rise by more than 3 • C. Recent research has shown that China's carbon-neutral target agrees well with the 1.5 • C warming limit [6,7].…”
Section: Introductionmentioning
confidence: 99%